Direct Clinical Evidence of Long-term Hard-tissue Repair after Miniature/ Tampon Pulpotomy: An Accidental Re-entry Case after Six Years - Asgary , Saeed; Roghanizadeh, Leyla; Eghbal, Mohammad Jafar (Iranian Endodontic Journal, 2026)
Vital pulp therapy (VPT) has become an established biologically-based treatment for preserving pulp vitality in mature permanent teeth with irreversible pulpitis. Although long-term clinical success has been widely reported, direct clinical evidence demonstrating the biological outcome beneath the pulp-capping material years after treatment is exceptionally rare because successfully treated teeth seldom require re-entry. A mature mandibular first molar diagnosed with symptomatic irreversible pulpitis associated with symptomatic apical periodontitis underwent a miniature pulpotomy. Because conventional hemostasis could not be achieved, the calcium-enriched mixture (CEM) cement tampon approach was used. Clinical and radiographic follow-up demonstrated resolution of symptoms, preservation of pulp sensibility, and progressive formation of a dentin bridge. Six years later, fracture of the coronal restoration necessitated restorative retreatment. Removal of the fractured restoration and residual CEM cement unexpectedly exposed the original pulpotomy site, revealing a continuous, mature mineralized dentin bridge that completely covered the pulp exposure. The tooth was conservatively restored, and one year later (seven years after the original treatment), it remained asymptomatic, responsive to pulp sensibility testing, and free of radiographic signs of periapical disease. This accidental re-entry provided a rare opportunity to directly visualize long-term hard-tissue repair following miniature pulpotomy with the CEM cement tampon approach. Together with sustained pulp vitality and complete periapical healing over seven years, this case provides uncommon clinical evidence supporting the long-term biological effectiveness of conservative VPT in mature permanent teeth.